Scientific Understanding of Kati Basti and its Application in Sciatica (Gridhrasi) - C P Verma,; Sushanta Kumar Sahoo, (International Journal of Ayurveda and Pharma Research, 2022)
Kati Basti is an Ayurvedic treatment approach that includes several acts such as Bahyasnehana (external oleation), and Swedana Chikitsa (fomentation therapy). Katibasti is not mentioned in any of the classical sources. Even though it is not injected into the body, it is nevertheless referred to as Basti because medicated and lubricated substances are applied to certain parts of the body for a set period. In Kati (back) and Adhah shakagata vikaras, Katibasti is beneficial (disorders of the lower part of the body). This type of external Basti is very beneficial for muscle spasms, lower back tightness, and bone tissue strengthening in the back area. Backache is the common term used for trending diseases of today's lifestyle due to the engagement of people in improper postures, one of them is sciatica. Sciatica (Gridhrasi) is a word for low back pain that travels down the inside of the leg, through the hip, to the back of the thigh, and down the inside of the leg. In general, 5-10% of people with low back pain have sciatica, but the lifetime prevalence of low back pain is believed to be between 49 and 70 percent. Modern science's treatment of sciatica is unsatisfactory, involving the use of analgesics for pain alleviation and surgical techniques that are frequently associated with side effects. Gridhrasi or sciatica is treated with a variety of methods described in Ayurveda. Kati Basti is a one-of-a-kind therapeutic technique due to its simple, non-invasive, and effective approach. The present review focus of Kati basti, its scientific understanding, its mode of action along its application in sciatica.